Understanding Performance Under Pressure: the Dual Role of Impostor Syndrome and Leader–Member Exchange In High-Tech Work Environments - Kusumawati, Retno; Murti, Tri; Yunanto, Kuncono (Indonesian Journal Publisher, 2025)
In examining the impact of digital transformation on employee performance, this study investigates how technostress and digital self-efficacy shape performance outcomes within a technology-integrated manufacturing company in Indonesia. It also assesses the mediating role of impostor syndrome and the moderating role of leader–member exchange (LMX). A quantitative design was applied, involving 236 employees whose responses were analyzed using Structural Equation Modeling (SEM) with R software. The results reveal that impostor syndrome does not function as a significant mediator for the overall sample, and LMX does not moderate the link between impostor syndrome and performance. Nevertheless, multigroup analysis shows that both mediation and moderation effects emerge among factory employees but not among office staff. These findings underscore the distinct psychological and relational dynamics that operate across different work settings in digitally driven manufacturing environments. The study provides practical implications for developing tailored organizational interventions that address digital stressors while strengthening leader–employee relationships to improve performance.